ACI and MACI - Kon, Elizaveta; Filardo, Giuseppe; Di Martino, Alessandro; Marcacci, Maurilio (The Journal of Knee Surgery, 2012)
Regenerative procedures aim to recreate a hyaline-like tissue, thus restoring a biologically and biomechanically valid articular surface with durable clinical results. Autologous chondrocyte implantation (ACI) has been developed two decades ago, and both the production of a hyaline-like articular surface and a satisfactory clinical outcome have been documented at medium-long follow-up. Bioengineering technology further improved this regenerative treatment approach to include matrix-assisted ACI (MACI) techniques. These procedures have been introduced in the clinical practice one decade ago, showing similar results while at the same time overcoming most of the concerns related to the first-generation ACI. The use of scaffolds to create a cartilage-like tissue in a three-dimensional culture system allows for the optimization of the procedure from both the biological and surgical point of view. However, despite thousands of treated patients and many published studies suggesting good clinical results and durability of these procedures, the properties of healthy, normal articular cartilage are still unmatched by any available substitute. Both indications and results of these substitutes are still controversial. The role of many variables that may influence the final outcome still need to be clarified to further improve the potential benefits of these biological regenerative procedures.
Keywords: cartilage regeneration; bioengineering; chondrocyte